2023
DOI: 10.1039/d2tb02280j
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine-coated 3D-printed β-tricalcium phosphate scaffolds to promote the adhesion and osteogenesis of BMSCs for bone-defect repair: mRNA transcriptomic sequencing analysis

Abstract: Cellular bioactivity and tissue regeneration can be affected by coatings on tissue-engineered scaffolds. Mussel-inspired polydopamine (PDA) is a convenient and effective approach to surface modification. Therefore, 3D-printed β-tricalcium phosphate (β-TCP)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…For example, liposomes that mimic biological membranes can be designed to encapsulate both hydrophilic and hydrophobic bioactive agents. Another example of bioinspiration is the mussel-inspired polydopamine (PDA) coating which is a convenient and effective approach to surface modification [269]. This strategy gives rise to effective nanocarriers for delivery bioactives like CUR [266].…”
Section: "Green" Approaches To Design Obnsmentioning
confidence: 99%
“…For example, liposomes that mimic biological membranes can be designed to encapsulate both hydrophilic and hydrophobic bioactive agents. Another example of bioinspiration is the mussel-inspired polydopamine (PDA) coating which is a convenient and effective approach to surface modification [269]. This strategy gives rise to effective nanocarriers for delivery bioactives like CUR [266].…”
Section: "Green" Approaches To Design Obnsmentioning
confidence: 99%
“…Moreover, in vitro and in vivo results indicated that PDA-mediated cell adhesion has a positive effect on cartilage tissue regeneration, and it could combine with CS-PAM to achieve synergistic effects for facilitating cartilage repair without growth factors ( Figure 8 ) (Han et al., 2018 ). Specifically, PDA coating could promote the adhesion, proliferation, and osteogenic differentiation of the bone marrow mesenchymal stem cells (BMSCs) through modulating the FAK signal pathway, p38 signal pathway, calcium signal pathway, Wnt signal pathway, and TGF-β signaling pathways (Wang et al., 2019 ; Sun et al., 2023 ).…”
Section: The Mechanism Of Pda In Adsmentioning
confidence: 99%